Plant Growth and Soil Microbial Impacts of Enhancing Licorice With Inoculating Dark Septate Endophytes Under Drought Stress - He, Chao; Wang, Wenquan; Hou, Junling (Frontiers in Microbiology, 2019)
This study mainly aimed to investigate the effects of dark septate endophytes (DSE) (Acrocalymma vagum, Paraboeremia putaminum, and Fusarium acuminatum) on the growth and microbial community composition in the rhizosphere soil of a medicinal plant, licorice (Glycyrrhiza uralensis), grown in the non-sterile soil under drought stress. The results showed that three DSE strains could effectively colonize the plant roots and form a strain-dependent symbiosis with licorice. Although drought stress declined the growth of licorice plants, these decreases were partly recovered by DSE inoculation. Specifically, the inoculation of A. vagum and P. putaminum significantly increased the biomass and glycyrrhizin content, whereas A. vagum and F. acuminatum increased glycyrrhizic acid content of host plants under drought stress. However, the inoculation of F. acuminatum showed significant negative effects on the shoot, root, and total biomass of licorice plants. In addition, the effects of DSE inoculation on the morphological, photosynthetic, and antioxidant parameters of licorice plants, and mineral nutrient and microbial community composition in the rhizosphere soil were dependent on the DSE species as well as water regime. Interestingly, DSE inoculation significantly increased AM fungi content under drought stress. In addition, DSE associated with water had a significant positive influence on soil organic matter, available phosphorus (P), AM fungi, leaf number, soluble protein, SOD activity, total root length, root branch, and glycyrrhizic acid content. Based on the results of variance partitioning analysis, 17.0, 34.0, 14.9, 40.1, 28.2, and 18.0% variations in shoot morphology, root morphology, plant biomass, active ingredient, photosynthetic parameters, and antioxidant parameters, respectively, were attributable to the presence of certain soil microorganisms. These findings suggest the possibility that DSE inoculation improved the root development and nutrient absorption of host plants, altered the soil microbiota, and might also contribute to plant growth and survival under drought conditions. As A. vagum exhibited positive effects on the plant biomass, morphological and physiological parameters, and active ingredient content in licorice plants under drought stress, it was considered to be the best fungus for licorice cultivation. These results contribute to the understanding of the ecological function of DSE fungi in dryland agriculture.